Low Sm doping effect on the low-field magnetoresistive properties in (La1-xSmx)0.67Sr0.33MnO perovskite - Lim, Kean Pah; Shaari, Abdul Halim; Chen, Soo Kien; Ng, Siau Wei; Zainuddin, Zalita; Ye, Chau Yuen (Universiti Putra Malaysia Press, 2009)
A series of polycrystalline samples (La1-xSmx) 0.67Sr0.33MnO3 (X=0.00, 0.05 and 0.10) were prepared using the conventional solid-state reaction method. The XRD analysis indicated that all the samples were fully crystalline and in a single phase with a rhombohedral structure after a sintering at 1200°C for 24 hours in air. Meanwhile, the Atomic Force Microscopy measurements showed that a small amount of Sm doping in La sites affected the grain growth and this might affect the grain boundary layer, thus resulting in the reduction of the Curie temperature, TC. Extrinsic magnetoresistance (MR) was observed for all the samples with a large negative MR at low field (0-0.1 or 0.2T) region, followed by a slower varying MR at high field (0.1 or 0.2-1T). The highest low-field MR value of -4.6% (at 0.1T) and -6.1% (at 0.2T) were observed for sample X=0.10 and X=0.05, respectively. Hence, these indicated that the extrinsic MR was grain size dependent and was therefore enhanced with a small amount of Sm substitution in La sites.